Ethos de formação por alternâncias na educação superior: ciclo formativo em uma universidade comunitária no RS - Hillesheim, Luis Pedro (Universidade do Vale do Rio dos Sinos, 2020)
The objective of this Thesis was to investigate the training practices by alternation, in a higher education course in the Agricultural area, located in the region of Médio Alto Uruguai, State of Rio Grande do Sul, Brazil. In this study, an attempt is made o problematize training by alternation and to analyze research data through studies by authors such as Zigmunt Bauman (2001, 2014, 2016), Richard Sennet (2009, 2013, 2000) and research authors, scholars of Pedagogy of Alternation such as Jean-Claude Gimonet (2007) and Gaston Pineau (2004), as well as studies on alternation training in formal and informal education connected to the world of work. The empirical material was composed by narratives of the graduates and teachers of the analyzed course, as well as analysis of the course documents. The option was to research training by alternating a higher education course characterized by regional productive diversification and from this to understand practices existing in different times and spaces of training between community and University. Results indicate that the Thesis that the training practices by alternations in higher education, make it easier to inseparable theory-practice, during the times-spaces community-university in movement, mobilized by training practices that constitute the alternation, therefore alternations and which is understood as a cycle of formation by alternations. This allows us to affirm that when articulating the pedagogical instruments with the times-spaces, community-university, the inseparable theory-practice is produced, developing the approach with the student's professional and life project, professional future, connected to the world of contemporary work, also built by student participation. Therefore, the cycle of training through alternations is created and creates a new educational culture, an ethos of training through alternations in higher education.
Keywords: Ethos de formação por alternâncias; Ciclo de formação por alternâncias; Pedagogia da alternância; Indissociabilidade teoria-prática; Práticas de formação por alternâncias; Ethos of formation by alternations; Formation cycle by alternations; Alternation pedagogy; Inseparable theory and practice; Alternation training practices; ACCNPQ::Ciências Humanas::Educação